2003
DOI: 10.1002/jat.918
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic character of thimerosal and the allometric extrapolation of adult clearance half‐time to infants

Abstract: The decomposition rate of organomercurials and the potency of the blood-brain barrier increase with the size of the organic radical. Thus methylmercury damages the brain more than thimerosal does, and when intake limits set for methylmercury are applied to thimerosal the safety margin is increased even if the clearances were the same. However, the clearance half-time of ethylmercury in adults is about one-third of the 50 days' clearance half-time of methylmercury given for 60 kg body weight. Moreover, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 17 publications
4
45
1
2
Order By: Relevance
“…This conclusion is the same as that reported by others in studies of infant monkeys (Burbacher et al, 2005), mice (Harry et al, 2004) and in rats (Magos et al, 1985;Magos, 2003). The many fold higher brain levels of organic mercury for methyl compared with the same dose of ethyl mercury is especially noteworthy.…”
Section: Discussionsupporting
confidence: 84%
“…This conclusion is the same as that reported by others in studies of infant monkeys (Burbacher et al, 2005), mice (Harry et al, 2004) and in rats (Magos et al, 1985;Magos, 2003). The many fold higher brain levels of organic mercury for methyl compared with the same dose of ethyl mercury is especially noteworthy.…”
Section: Discussionsupporting
confidence: 84%
“…Desde hace varios años, estudios in vivo hechos en roedores habían mostrado que el etilmercurio era capaz de atravesar las membranas celulares y luego ser convertido intracelularmente a Hg inorgánico, el mismo que se acumula preferentemente en el cerebro y los riñones. Dicha acumulación intracelular de Hg inorgánico demostró ser mayor para el etilmercurio (timerosal), en relación al metilmercurio empleando exposiciones equimolares, pese a que la velocidad de depuración sanguínea del etilmercurio es definitivamente más rápida que la del metilmercurio ( 152 ). No obstante, se ha determinado que no existen mayores diferencias entre la toxicidad del metilmercurio y el timerosal.…”
Section: Estudios En Modelos Animalesunclassified
“…However, some studies have not shown significant adverse effects from methylmercury exposure (Marsh, Turner, Smith, Allen, & Richdale, 1995;McKeown-Eyssen, Ruedy, & Neims, 1983;Myers et al, 2003). One animal study has shown differential neurotoxic effects between ethylmercury and methylmercury (Magos, 2003), suggesting ethylmercury may be less toxic due to increased protective potency of the blood brain barrier as well as a shorter half life. In addition to the results of MMR vaccine epidemiological studies, although thimerosal has been largely removed from vaccines in the United States since 1999, increases in autism prevalence has remain unchanged.…”
Section: Alternative Theoriesmentioning
confidence: 99%